Intervenção didática para produção de narrativas a partir da adaptação de um jogo de tabuleiro - Dantas, Rawêna de Almeida Araújo (2021)
Many difficulties are presented by students when it comes to the construction of knowledge regarding the production of written texts. These difficulties have been revealed through the recording of the students' own orality, confirmed by means of instruments of assessment which have been used by mother tongue teachers during their classes and reaffirmed by quantitative data expressed in the results of assessments performed by the Ministry of Education. Based on this problematic issue, we propose an adaptation of the board game “Where's Mr. Smitch?” to be used as a didactic tool by the Portuguese teacher to favour the students' understanding of narrative writing in a more dynamic and pleasurable way, resulting in a less resistant and more effective internalization of the written narratives competences. As an educational product, we have the game “Where is Luciana?”, used in the research undertaken at Murilo Braga Elementary and Secondary Education Public School, located in the Liberdade neighbourhood, in the city of Campina Grande, with a group of 5 (five) students from the 6th grade. It is a didactic intervention done remotely, given the socio-historical context in which we are inserted due to the COVID-19 pandemic, although three of the eleven meetings that make up the didactic proposal have taken place in a face-to-face mode, since it was the board game performance. We therefore have a research with the objective to favour the production of narrative texts written by 6th grade students, from the Elementary School Final Years, through a board game used by the Portuguese teacher as a didactic intervention instrument. As an object of study, we used 4 (four) written production suggested through activities done during the interventions, which were carried out by each of the collaborating students. Using a qualitative approach, we were immersed in the context of the research, and through an interventional research of an applied nature and of an exploratory and bibliographic type, we sought new knowledge about teaching practice related to our object of research, linked to the theories that conduct the written text production, focusing on the narrative, through the theoretical support of Gancho (2006), Bronckart (1999), based on the studies of Adam (1992), Brandão (2000), Cardoso (2009), Reales (2008) and Ginzburg (2000); as well as the game as a didactic-pedagogical instrument, based on Teixeira & Apresentação (2014), Kishimoto (1996), Macedo (2000), Smole (2008) and Brougère (1998). Therefore, we believe that our educational product (the board game “Where is Luciana?”) is a didactic-pedagogical instrument which favours the consolidation of the learning of the narrative texts production. This is possible once it enables the appearance and / or improvement of the elements that form the narratives, marked by macro textual elements related to the whole and to the events narrated from the textual structure of the plot.